Anatomical and variation of physical properties in the axial direction of three bamboo species in the eastern Amazon of Peru - Portal-Cahuana, Leif Armando (2023)
Bamboos are abundant and versatile, hence their growing interest throughout the world in a variety of uses, however, there is little technical information on the anatomy and physical properties that are important to further expand and diversify its uses. For them, the objective was to characterize the anatomy and variation in the axial direction of the physical properties of the three bamboo species in the Madre de Dios region. For this, the bamboo species were collected: Bambusa vulgaris, Gigantochloa apus, and Guadua weberbaueri were through destructive methods, collecting three culms from different bushes and obtaining samples at different heights of the culm (base, intermediate and apex). The anatomy was performed at the base of the culm and the physical properties at the three axial positions. The results show that at the anatomical level, there is a difference between the three species mainly due to the vascular bundles, on the physical properties there was also a difference between species and the variation in the axial direction there was variation in the three positions, in addition, the grouping analysis showed that the species Bambusa vulgaris and Gigantochloa apu form a group due to their anatomical characteristics and physical properties, while Guadua weberbaueri was not grouped with either. Finally, the appropriate uses of the three bamboo species are directly related to their anatomy and physical properties, being key to their sustainable use in tropical forests.